THE EFFECT OF BANK HEALTH OF THE RGEC METHOD ON THE VALUE OF ASEAN BANKING COMPANIES 2021–2023: Array - Bambang Sugiharto; Nurlaila Maesaroh; Sri Mulyati (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2025)
This research aims to find out how the Bank’s Health Level influences Firm Value. The indicators in this research are Risk Profile measured using Loan to Deposit Ratio, Good Corporate Governance measured using Self Assessment, Earnings measured using Return on Assets, and Capital measured using the Capital Adequecy Ratio. The population used in this research is conventional banking subsector companies listed on the ASEAN Exchange for the 2021-2023 period. This research is a quantitative type of research with a sample selection method using a purposive sampling technique, and 150 data were obtained. The analytical method used in this research is multiple regression analysis. The research results show that the Loan to Deposit Ratio, Good Corporate Governance, and Capital Adequacy Ratio variables have no effect on Firm Value, while the Return on Assets variable influences Firm Value.